Affiner la description des termes dans les dictionnaires généraux : l’apport d’un corpus de vulgarisation - Amélie Josselin-Leray (Lexis: Journal in English Lexicology, 2010)
The aim of the paper is to show how useful a popular-science corpus can be to improve the inventory and description of terminological units in general-purpose dictionaries. The article first discusses the role of corpora in general-purpose lexicography and explains how they are used in the dictionary-writing process. In the second section of the article, the methodology used in this study is described. The study, which focuses on the field of volcanology, compares the data found in six general-purpose dictionaries (two English monolingual dictionaries, two French monolingual dictionaries, and two French/English bilingual dictionaries) to those found in two popular-science corpora (one French/English comparable corpus, and one bi-directional translation corpus). The first part of the analysis deals with the macrostructure of the dictionaries, and determines how many terms (among the 220 picked in the comparable corpus–110 per language) are listed and what types of terms they are. The second part focuses on the microstructure, and shows how resorting to a corpus can improve the grammatical indications, definitions and equivalents of a number of terms.